STUDI PERILAKU PELINDIAN BIJIH NIKEL LIMONIT DARI PULAU HALMAHERA DALAM LARUTAN ASAM NITRAT [Study on the Leaching Behaviour of Limonite Nickel Ore From Halmahera Island in Nitric Acid Solution] - Fathoni, Mohammad Wildanil; Mubarok, Mohammad Zaki (Jurnal Metalurgi, 2015)
Efforts to reduce the consumption of leaching agent either by increasing selectivity of nickel laterite ore leaching and regeneration of the leaching agent, are being the focus of researchers and industries in recent years. One of technologies that is developed is the leaching of laterite ore in nitric acid, through which more than 95% of nitric acid being used can be regenerated. In this paper, leaching behavior of nickel laterite ore from Halmahera Island is discussed. A series of leaching experiments in nitric acid solution has been carried out under variations of nitric acid concentration, solid percentage and temperature. Analysis using experimental factorial design of 23 was performed to determine the effects of temperature, acid concentration and solid percentage as well as the interaction between these variables toward nickel extraction during leaching. The experimental results show that the highest nickel extraction of 94%, was obtained from the leaching test for 8 hours using acid concentration of 6 M, 10% solid at temperature of 95 °C. The most influencing variable on nickel extraction is temperature with contribution of 78%. Selectivity of Ni leaching to Fe and Mg is relatively low, with average values of SNi/Fe and SNi/Mg of 0.53 and 0.50, respectively. Acid consumption in leaching process is relatively high, which the highest consumption was at leaching temperature of 95 °C, acid concentration 4 M and 10% solid, namely 1010 kg/ton ore.